A „per viam instantiae” perek az erdélyi református házassági jogban - Nagy, Péter (Díké - A Márkus Dezső Összehasonlító Jogtörténeti Kutatócsoport folyóirata, 2021)
This article aims to analyse the “per viam instantiae” cases in the matrimonial jurisdiction of the Reformed Church in Transylvania. Until the introduction of civil marriages in 1895, denominations had the right to declare the marriage of their members in Transylvania in the second half of the nineteenth century. All this time, in the motherland, these cases fell under the jurisdiction of civil courts, and the canon law did not recognise the dissolution of marriage. Therefore, it was easier to get divorced in Transylvania than in the other parts of the Austro-Hungarian Empire. Due to this difference between the rules in the field of matrimonial law, the matrimonial courts of the protestant churches were the goal and an opportunity for the people who wanted to get divorced.